Handbook of Secondary Fungal Metabolites, 3-Volume Set - Cole, Richard J. (Academic Press, 2021)
This three-volume set is a desirable reference for a wide range of specialists who study secondary fungal metabolites ranging from pharmaceutical house researchers, agricultural researchers, those involved in food and feed control regulation, and veterinary researchers. It discusses in depth the molecular formula of, the molecular weights of, and fungal/plant source indexes of secondary fungal metabolites.